1993
DOI: 10.1159/000113852
|View full text |Cite
|
Sign up to set email alerts
|

Agonistic Behavior and Its Cardiovascular Components Elicited by Microinjection of L-glutamic Acid into the Basal Midbrain of the Toad <i>Bufo paracnemis</i>

Abstract: Microinjection of L-glutamic acid into the basal midbrain of the toad Bufo paracnemis induced a series of responses linked to antipredator behavior such as flight, backward locomotion and defensive postures. Furthermore, alerting/ orientation occurred in 20% of the animals, a behavior which is probably important for the animal to achieve the above responses. Locomotion occurred in 18% of the toads. The existence of a mesencephalic premotor control for locomotion in these animals is discussed comparatively. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…In mammals, it has been demonstrated that sensory collicular input from a given spatial location is not used only for orientation but also to generate a motor output critical for survival. In toads of the genus Bufo, chemical or electrical stimulation of the torus semicircularis induces species-specific defensive responses (28,37). We therefore postulate that collicular control of defense systems is a phylogenetically old, retained mechanism since it is common to representatives of all vertebrate groups studied.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In mammals, it has been demonstrated that sensory collicular input from a given spatial location is not used only for orientation but also to generate a motor output critical for survival. In toads of the genus Bufo, chemical or electrical stimulation of the torus semicircularis induces species-specific defensive responses (28,37). We therefore postulate that collicular control of defense systems is a phylogenetically old, retained mechanism since it is common to representatives of all vertebrate groups studied.…”
Section: Discussionmentioning
confidence: 95%
“…Defense-like reactions can be obtained from these regions by a variety of stimulating agents, including GABA blockers and excitatory amino acids (26,27). Glutamate microinjected into the regions of the mesencephalic tegmentum near the TS of the toad Bufo paracnemis induces a flight response (28).…”
Section: Tt Duarte Et Almentioning
confidence: 99%